Prediction of Load-Settlement Curves by the DMT in an Unsaturated Tropical Soil Site - Silva, N. M.; Rocha, B. P. [UNESP]; Giacheti, H. L. [UNESP] (Brazilian Soc Soil Mechanics & Geotechnical Engineering, 2019)
Several methods for prediction of the load-settlement curves of shallow foundations have been proposed based on in-situ testing data. However, the good accuracy of such prediction depends on the definition of appropriate soil stiffness. Seasonal variability and its influence on the soil behavior need to be considered for unsaturated tropical soils. In this context, this study uses a procedure to determine the complete load-settlement curves of shallow foundations by the flat dilatometer test (DMT) in an unsaturated tropical soil site, considering seasonal variability. The DMT and the plate load tests carried out at the experimental research site of the University of Sao Paulo (Sao Carlos, Brazil) are presented and discussed. It was found that the DMT is an adequate test for predicting soil stiffness, and the presented procedure allows a good estimate of the complete load-settlement curves. It was also observed that seasonal variability should be considered in the prediction of such curves for the studied site.
Keywords: flat dilatometer test (DMT); in-situ tests; load-settlement curve; seasonal variability; tropical soils